Bahasa Inggris - Rahayu, Silvia; Evanita, Susi (Journal of Business Studies and Management Review, 2024)
This research aims to determine environmental communication strategies for sustainable waste management through community empowerment. This research was conducted in Talang Lindung Village, Sungai Bungkal District, Sungai Penuh City. The research results showed that community empowerment in managing household waste and maintaining environmental cleanliness began to improve with mass communication and personal communication activities. Mass communication was carried out through FGDs and placing banners in several strategic places in Talang Lindung Village, while personal communication was carried out by providing door-to-door counseling and distributing brochures. To determine changes in knowledge, attitude and behavior of the community after mass and personal communication, evaluation and monitoring were carried out in collaboration with the Head of Talang Lindung Village. The results of this research show that changes in personal communication behavior are more influential than mass communication. From the results of evaluation and monitoring, it is known that mass communication can be used to increase knowledge, but behavior change is more influential if personal communication is used. With mass communication through FGDs and the installation of banners, people who previously did not know became aware that there are laws and regulations governing waste disposal.